KONTRIBUSI KAJIAN KEAGAMAAN DALAM SOSIOLOGI ISLAM - Asnawan Asnawan (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
This article describes about sociology approach in the religious aspect. Besides in, it’s question the function of and developing of social integrations or religious social movements. In this context, it’s very important to understanding religiuos phenomenon that has happened in society, because of attitude and behaviour is aplicated of personal attitude religious. Normatively, in the verses of holly quran which has said and explored is only about muamalah or social problem.